Pertumbuhan Mucuna bracteata DC. pada Berbagai Waktu Inokulasi dan Dosis Inokulan - Laksono, Purwanti Budi; Wachjar, Ade; Supijatno, dan (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2016)
ABSTRACTMucuna bracteata DC. is a legume cover crop to prevent erosion and to suppress weed growth. M. bracteata can fix N2 from the air with the help of Rhizobium. M. bracteata get benefit from the symbiosis in the form of increased nodule weight, shoot dry weight, and leaf nitrogen content when the Rhizobium population in the soil is optimal. Application of inoculant is one method to increase the Rhizobium population in the soil. This study aimed to analyze the effects of inoculation times and inoculant rates on M. bracteata growth. The research was conducted in Boyolali, Central Jawa, from February to August 2014. The inoculant contained Bradyrhizobium japonicum and Aeromonas punctata. This experiment was arranged in a randomized block design with two factors and three replications. The first factor was two inoculation times, i.e at the nursery when the seedlings were 2 weeks old and in the field when the seedlings reached 5 weeks old. The second factor was 5 inoculant rates (0, 2, 4, 6, and 8 g per plant). The results showed that inoculation on 5-week-old seedlings was the best result compared to the 2-week-old seedlings. The recommended inoculant rate for Mucuna bracteata was 6.43 g per plant. Keywords: legume cover crop, nitrogenase activity, nodule, nutrient content, runner